2017
DOI: 10.1002/pssa.201600603
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of m‐plane ZnO films formed on buffer layers on sapphire substrates by mist chemical vapor deposition

Abstract: The crystal quality of ZnO films grown by mist chemical vapor deposition (mist‐CVD) was improved by introducing ZnO buffer layers on sapphire substrates. The ZnO films were grown by high‐speed rotation‐type mist‐CVD with a ZnCl2 aqueous solution, which provided uniform epitaxial layers over 2‐inch wafers. To grow the ZnO buffer layers, it is necessary to form small grains of polycrystal. Therefore, we attempted to grow the ZnO buffer layers using a Zn(CH3COO)2 aqueous solution, which provides a small grain siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…As such, mist-CVD is regarded as relatively simple, safe and cost-effective. [10][11][12][13][14][15][16][17][18] Recent years have witnessed mist-CVD delivering on their promise of high-quality metal-oxide thin films and demonstrating their capability as an able replacement for vacuum deposition techniques. For Al 2 O 3 thin films deposited by mist-CVD, Kawaharamura et al 10) reported AlO x thin films having smooth surface grown on 100 mm j substrates.…”
mentioning
confidence: 99%
“…As such, mist-CVD is regarded as relatively simple, safe and cost-effective. [10][11][12][13][14][15][16][17][18] Recent years have witnessed mist-CVD delivering on their promise of high-quality metal-oxide thin films and demonstrating their capability as an able replacement for vacuum deposition techniques. For Al 2 O 3 thin films deposited by mist-CVD, Kawaharamura et al 10) reported AlO x thin films having smooth surface grown on 100 mm j substrates.…”
mentioning
confidence: 99%
“…The appearance of additional growth directions like. e.g., (10.3) was observed previously for ZnO layers grown on the m -plane Al 2 O 3 substrates by various methods , and also in {CdO/ZnO} SLs . Kim et al observed for pure ZnO layers obtained by PA-MBE at different growth temperatures the highest intensity ratio of 10.0/10.3 for growth temperatures between 400 and 500 °C, and decreases of this ratio for the relative low and high growth temperatures (100 and 800 °C).…”
Section: Resultsmentioning
confidence: 63%
“…In our previous study of ZnO, we fabricated uniform ZnO(1 100) epitaxial layers by mist-CVD on sapphire (1 100) substrates. 5,6) According to this result, the ZnO buffer layers were formed under similar conditions; namely, using an aqueous source solution of ZnCl 2 (0.1 mol=L, 50 mL). The ZnO buffer layers were grown at 600 °C with a gas flow rate of 8 L=min.…”
Section: Resultsmentioning
confidence: 91%
“…Oxide thin films such as zinc oxide (ZnO), tin oxide, and other metal oxides are easily formed using mist-CVD because oxygen of H 2 O molecule in the mist generated from the aqueous solutions reacts with the metal elements on the surface of the heated substrate. [5][6][7][8][9][10][11] Recently, sulfides such as zinc sulfide (ZnS) have been formed via mist-CVD by adding sulfur-containing materials such as thiourea. [12][13][14] ZnS is an abundant material and a wide-bandgap compound semiconductor from group II-VI.…”
Section: Introductionmentioning
confidence: 99%